Tears of the giraffe - McCall Smith, Alexander, 1948- (McCall Smith, Alexander, 1948- No. 1 Ladies Detective Agency series., 2002)
Among her cases this time are wayward wives, unscrupulous maids, and the challenge to resolve a mother's pain for her son who is long lost on the African plains. Indeed, Mma Ramotswe's own impending marriage to the most gentlemanly of men, Mr J.L.B. Matekoni, the promotion of Mma's secretary to the dizzy heights of Assistant Detective, and the arrival of new members to the Matekoni family, all brew up the most humorous and charmingly entertaining of tales.